Keberlanjutan Usaha Melalui Pengelolaan Keuangan: Analisis SOAR Pada IKM Fashion di Pancur Batu - Siti Nurhaliza; Muhammad Syahbudi; Wahyu Syarvina (POLITEKNIK LP3I, 2026)
This study aims to analyze business sustainability strategies through financial management in fashion SMEs in Pancur Batu District using the SOAR (Strengths, Opportunities, Aspirations, Results) approach. A descriptive qualitative method was employed, with data collected through interviews, observations, and documentation from purposively selected informants, including academics, business owners, and business community members. The findings indicate that SMEs possess strengths in production competence, customer loyalty, and operational flexibility, while digital technology and social media create significant growth opportunities. The recommended strategies emphasize strengthening financial management, improving financial literacy, implementing systematic financial record-keeping, optimizing digital technology, and expanding business networks. The SOAR approach proves effective in supporting sustainable SME development.